2013
DOI: 10.1002/adfm.201202571
|View full text |Cite
|
Sign up to set email alerts
|

Charge‐Compensated Compound Defects in Ga‐containing Thermoelectric Skutterudites

Abstract: Heavy doping changes an intrinsic semiconductor into a metallic conductor by the introduction of impurity states. However, Ga impurities in thermoelectric skutterudite CoSb3 with lattice voids provides an example to the contrary. Because of dual‐site occupancy of the single Ga impurity charge‐compensated compound defects are formed. By combining first‐principle calculations and experiments, we show that Ga atoms occupy both the void and Sb sites in CoSb3 and couple with each other. The donated electrons from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
106
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 111 publications
(121 citation statements)
references
References 54 publications
14
106
0
Order By: Relevance
“…23) Our group also has studied the TE properties of Ga-, In-, and Tl-filled skutterudites and confirmed that the group 13 elements filledskutterudites exhibit low ¬ lat and thereby relatively high ZT values. 2426) In particular, the maximum values of ZT of 0.9 and 0.7 at 600 K have been obtained for Tl-and In-filled skutterudites, respectively.…”
Section: Introductionsupporting
confidence: 53%
“…23) Our group also has studied the TE properties of Ga-, In-, and Tl-filled skutterudites and confirmed that the group 13 elements filledskutterudites exhibit low ¬ lat and thereby relatively high ZT values. 2426) In particular, the maximum values of ZT of 0.9 and 0.7 at 600 K have been obtained for Tl-and In-filled skutterudites, respectively.…”
Section: Introductionsupporting
confidence: 53%
“…is the density of states of ideal host cell, and is the Fermi-Dirac distribution given by: 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 13 (8) Following the procedure described above, the Fermi level (E F ) and free carriers can be determined by iteratively solving the overall charge neutrality requirement, as displayed in 17 The annealing temperature region of CoSb 3 is generally around 850 -1100 K. [14][15][16][17][18][19][20][21][22][23] The electron carrier concentration is found to be The total composition x of a phase with defects within an equilibrium set of atomic chemical potentials can be calculated by:…”
Section: Defect Carrier Concentration and Solubility Limitation In M mentioning
confidence: 99%
“…The unit cell contains two structural cages that can be filled by a variety of guest atoms such as rare earth elements, [4][5][6][7] alkaline earth metals, [8][9][10] alkali metals, 11,12 and group 13 elements. [13][14][15][16][17] When the guest atom denoted by R is incorporated into the cages, the general formula of the compounds, referred to as filled skutterudites, becomes RM 4 × 12 .…”
mentioning
confidence: 99%